Effect of Autogenic Relaxation on Blood Pressure Reduction in Elderly Patients with Hypertension - Sumantrie, Pipin; Limbong, Martalina (Proceeding - Sari Mutiara Indonesia International Conference on Health, 2018)
A large number of people who do not know that the mind is not calm or relaxed is closely related to the rise in blood pressure or hypertension. Hypertension until now is still one of the major health problems in public health in developed countries and in developing countries. Hypertension can be treated with pharmacological and nonpharmacological treatments. One of nonpharmacologic treatment is autogenic relaxation to hypertension blood pressure. The method used by the writer is Quasi Eksperimen Design with pre and post, which is a design that gives treatment to the group, then observed before and after implementation. The population of all elderly with hypertension, the sample consists of 10 respondents. Independent variable is autogenic relaxation and the dependent variable is hypertension in parent or elderly. The data collected through observation was analyzed by paired t-test statistic with significance level α = 0,05. The result of the analysis showed that there was a change of mean pressure between before and after autogenic relaxation therapy with significant systole value at p-Value = 0,04 (α <0,05) and diastol significant value at p-Value = 0,01 ( α <0.05) so that there is an autogenic relaxation effect on the decrease in blood pressure in the elderly patients with hypertension. In conclusion, seeing the results of this study then this autogenic relaxation therapy can be used as an alternative therapy in treating blood pressure problems in elderly or parents in addition to treatment therapy.